Outcome of Early Dental Implant Placement Versus Other Dental Implant Placement Protocols: A Systematic Review and Meta-analysis - Bassir, Seyed Hossein (J Periodontol, 2018)
BACKGROUND: The aim of this systematic review and meta-analysis was to compare the clinical efficacy of the early dental implant placement protocol with immediate and delayed dental implant placement protocols. METHODS: An electronic and manual search of literature was made to identify clinical studies comparing early implant placement with immediate or delayed placement. Data from the included studies were pooled and quantitative analyses were performed for the implant outcomes reported as the number of failed implants (primary outcome variable) and for changes in peri-implant marginal bone level, peri-implant probing depth, and peri-implant soft tissue level (secondary outcome variables). RESULTS: Twelve studies met the inclusion criteria. Significant difference in risk of implant failure was found neither between the early and immediate placement protocols (Risk difference=−0.018; 95%CI=−0.06, 0.025; p=0.416) nor between early and delayed placement protocols (Risk difference=−0.008; 95%CI=−0.044, 0.028; p=0.670). Pooled data of changes in peri-implant marginal bone level demonstrated significantly less marginal bone loss for implants placed using the early placement protocol compared with those placed in fresh extraction sockets (p=0.001; Weighted Mean Difference=−0.14 mm; 95%CI=−0.22, −0.05). No significant differences were found between the protocols for the other variables. CONCLUSION: The available evidence supports the clinical efficacy of the early implant placement protocol. Present findings indicate that the early implant placement protocol results in implant outcomes similar to immediate and delayed placement protocols and a superior stability of peri-implant hard tissue compared to immediate implant placement.